2022
DOI: 10.3390/genes13101825
|View full text |Cite
|
Sign up to set email alerts
|

Current Analytical Methods and Research Trends Are Used to Identify Domestic Pig and Wild Boar DNA in Meat and Meat Products

Abstract: The pig, one of the most important livestock species, is a meaningful source of global meat production. It is necessary, however, to prove whether a food product that a discerning customer selects in a store is actually made from pork or venison, or does not contain it at all. The problem of food authenticity is widespread worldwide, and cases of meat adulteration have accelerated the development of food and the identification methods of feed species. It is worth noting that several different molecular biology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 86 publications
0
0
0
Order By: Relevance
“…It should be noted that in the event that one needs to detect several species simultaneously in one reaction, more than one digestion enzyme usually needs to be used. Nevertheless, the method itself is qualitative, very sensitive, quite cost-effective and has been successfully applied to various mixed products, which is why it is still used as the preferred method in various laboratories (Table 2) [22].…”
Section: Polymerase Chain Reaction-restriction Fragment Length Polymo...mentioning
confidence: 99%
“…It should be noted that in the event that one needs to detect several species simultaneously in one reaction, more than one digestion enzyme usually needs to be used. Nevertheless, the method itself is qualitative, very sensitive, quite cost-effective and has been successfully applied to various mixed products, which is why it is still used as the preferred method in various laboratories (Table 2) [22].…”
Section: Polymerase Chain Reaction-restriction Fragment Length Polymo...mentioning
confidence: 99%
“…Microsatellite markers are simple sequence repeats of highly polymorphic and codominant DNA motifs (n could range from 8 to 50) that are widely distributed throughout the genomes of eukaryotes and are widely used for different population genetic studies in many different species, such as genetic diversity [ 27 , 28 , 29 ], population structure, parentage determination [ 30 , 31 , 32 ], and constructing genetic linkage maps [ 33 , 34 , 35 , 36 , 37 ], animal identification, meat traceability [ 38 , 39 ] and animal breeding [ 40 , 41 ]. Studies on related aquatic species with highly duplicated genomes have demonstrated that microsatellites derived from transcriptomes are significantly more effective than those developed from the genome using traditional methods [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mislabeling and fraud meat processed products harm and decrease consumer trust [1]. The adulteration of pork or wild boar meat in food concerns researchers to obtain the appropriate and accurate methods for identifying both [2]. In Western societies, pork is frequently consumed as an animal protein source.…”
Section: Introductionmentioning
confidence: 99%